2015
DOI: 10.2217/pgs.15.77
|View full text |Cite
|
Sign up to set email alerts
|

Discussing the Putative Role of Obesity-Associated Genes in the Etiopathogenesis of Eating Disorders

Abstract: In addition to the identification of mutations clearly related to Mendelian forms of obesity; genome-wide association studies and follow-up studies have in the last years pinpointed several loci associated with BMI. These genetic alterations are located in or near genes expressed in the hypothalamus that are involved in the regulation of eating behavior. Accordingly, it seems plausible that these SNPs, or others located in related genes, could also help develop aberrant conduct patterns that favor the establis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 189 publications
(231 reference statements)
0
8
0
Order By: Relevance
“…But, what would be the precise mechanism linking this gene to these behaviors and specifically to ED? These personality features are expressed by the involvement of a pattern of neuronal adaptations induced by central genes such as dopamine or serotonin, which has been consistently associated with ED‐coupled personality dimensions (Gervasini & Gamero‐Villarroel, 2015). Dopaminergic and serotonergic genes in the midbrain have AP‐2 binding sites; therefore it is likely that these transcription factors, aside from its established role during development, can also influence mood and personality in adults through this neurotransmitter system (Damberg, 2005; Damberg et al., 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…But, what would be the precise mechanism linking this gene to these behaviors and specifically to ED? These personality features are expressed by the involvement of a pattern of neuronal adaptations induced by central genes such as dopamine or serotonin, which has been consistently associated with ED‐coupled personality dimensions (Gervasini & Gamero‐Villarroel, 2015). Dopaminergic and serotonergic genes in the midbrain have AP‐2 binding sites; therefore it is likely that these transcription factors, aside from its established role during development, can also influence mood and personality in adults through this neurotransmitter system (Damberg, 2005; Damberg et al., 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Genetic alterations in the complex neural system aimed to keep energy balance by food intake are known to trigger and maintain obesity, but the genes involved in the neuronal control of weight regulation might also be relevant for ED (Day, Ternouth, & Collier, 2009; Gervasini & Gamero‐Villarroel, 2015). Indeed, we and others have shown that variability in these genes is also associated with ED‐related behaviors (Gamero‐Villarroel et al., 2014, 2015; Muller et al., 2012; Rybakowski et al., 2007).…”
Section: Introductionmentioning
confidence: 99%
“…However, plasma levels of NPY (part of the orexigenic system) are anomalously low [96]. Abnormalities within the hormonal regulation of the homeostatic system have also been reported for BN [111] and BED [112].…”
Section: Neural Circuits and Neurotransmittersmentioning
confidence: 99%
“…MC4R and BDNF were found to be highly expressed in the hypothalamus, which suggests that they may play important roles in the central nervous system in eating behavior [15, 16]. Golden et al reported that the BDNF level was inversely correlated with adiponectin in adult males [17].…”
Section: Introductionmentioning
confidence: 99%